Une institution en crise: les chaires «grecques» dans les universités étrangères - Prevelakis, Georges (Études helléniques / Hellenic Studies, 2006)
The Greek chairs abroad certainly generate interest in Greece. However, the international public pays only scant attention to the activities of these chairs which, moreover, are losing students. Overall the result is both frustrating and disappointing. The author presents the recent, often contradictory, efforts made to revive interest in these chairs. He suggests three possible avenues for the government and foundations to follow when helping to promote the image of Greece abroad. His suggestions include relinking modern Greek studies to classics by supporting efforts to defend and promote the discipline; providing timely funding through research projects related to modern Greece and its diaspora rather than creating new chairs and centres; linking university structures already in place with local Greek diaspora communities and their socio-political milieus and reorienting their missions toward multicultural issues.